Идейный контекст повести Владимира Сорокина «День опричника» - Kalafatics , Zsuzsanna (SlavVaria, 2022)
The ideological context of Vladimir Sorokin's novel Day of the Oprichnik This article explores the ideological context of Vladimir Sorokin's dystopia, written in 2006. It examines how questions of national identity and the mass myths of the totalitarian state are embedded in the world of the novel, and how Ivan the Terrible's oprichnina becomes a timeless and extra-historical universal model. The story of Komiaga’s one day is a story about the mechanisms of power and violence of an authoritarian type, shown from the point of view of a member of the state apparatus. The analysis presents rituals that rein-force a sense of community, as well as issues related to the use of language and the role of literature.